Oxidative Stress in the Blood Labyrinthine Barrier in the Macula Utricle of Meniere’s Disease Patients - Ishiyama, Gail; Wester, Jacob; Lopez, Ivan A.; Beltran-Parrazal, Luis; Ishiyama, Akira (Frontiers in Physiology, 2018)
Recent studies in Meniere’s disease (MD) using imaging and histopathological studies show breakdown of the blood labyrinthine barrier in the affected inner ear of Meniere’s patients. We hypothesize that oxidative stress is involved in the pathogenesis of BLB degeneration, and to date there are no studies of oxidative stress proteins in the human BLB. We investigated ultrastructural and immunohistochemical changes of the BLB in the macula utricle from patients with MD (n=10), acoustic neuroma (AN) (n=6) and normative autopsy specimens (n=3) with no inner ear disease. Each subject had a well-documented clinical history and audiovestibular testing. Utricular maculae were studied under light, and transmission electron microscopy and double labeling immunofluorescence. Vascular endothelial cells (VEC) were identified using isolectin B4 (IB4) and glucose-transporter-1 (GLUT-1). Pericytes were identified using alpha smooth muscle actin (SMA) and phalloidin. IB4 staining of VECS was consistently seen in both AN and normative. In contrast, IB4 was nearly undetectable in all Meniere’s disease specimens, consistent with the significant VEC damage confirmed on transmission electron microscopy. GLUT-1 was present in MD, AN, and normative. SMA and phalloidin were expressed in the BLB pericytes in normative and AN specimens, and there was robust expression in the pericytes of Meniere’s specimens. Endothelial nitric oxide synthase (eNOS), inducible nitric oxide synthase (iNOS), and nitrotyrosine were used as markers of oxidative stress. The VECs of the BLB in MD had significantly higher levels of expression of iNOS and nitrotyrosine compared with normative and AN specimens. eNOS-IF staining showed similar patterns in normative and MD specimens. Microarray-based gene expression profiling demonstrated upregulation of iNOS mRNA from the macula utricle of MD patients compared with AN. Nitrotyrosine, a marker recognized as a hallmark of inflammation, especially when seen in association with an upregulation of iNOS, was detected in the epithelial and stromal cells in addition to VECs in MD. In summary, immunohistochemical and ultrastructural degenerative changes of the vascular endothelial cell suggest that these cells are the primary targets of oxidative stress in MD specimens.